Analysis of the Application of the Code of Ethics and Criminal Sanctions Against Advocates Receiving Bribery - Karyn, Khanza Octalivia; Natalie, Cicilia; Milianty, Yessa; Anindira, Lydia; Sukawan, Wanda Putri (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
Indonesia is a constitutional state that upholds justice. Advocates as one of the law enforcement officers who have an important role in maintaining justice and the integration of the legal justice system should not be ethical to accept bribes from any party, but it cannot be denied that there are still unscrupulous advocates who accept bribes and tarnish their professional code of ethics. This study uses a normative juridical method with a statutory approach related to the problem of bribery criminal sanctions against advocates. Advocates who accept bribes not only harm the fundamental principles that underlie the legal system but also damage the entire public's trust in the advocate profession and the justice system as a whole. Sanctions for unscrupulous advocates who accept bribes include revocation of their advocate license, disciplinary action, and criminal sanctions. Bribery in any form is unacceptable and must be eradicated immediately so that justice is protected in the justice system.